2014
DOI: 10.4171/rmi/791
|View full text |Cite
|
Sign up to set email alerts
|

Stable polynomials over finite fields

Abstract: Abstract. We use the theory of resultants to study the stability of an arbitrary polynomial f over a finite field F q , that is, the property of having all its iterates irreducible. This result partially generalises the quadratic polynomial case described by R. Jones and N. Boston. Moreover, for p = 3, we show that certain polynomials of degree three are not stable. We also use the Weil bound for multiplicative character sums to estimate the number of stable arbitrary polynomials over finite fields of odd char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…We also note that in [8] an upper bound is given on the number of stable polynomials of degree d 2 over F q .…”
Section: Introductionmentioning
confidence: 99%
“…We also note that in [8] an upper bound is given on the number of stable polynomials of degree d 2 over F q .…”
Section: Introductionmentioning
confidence: 99%
“…For proving our results, we treat the discriminant of a general polynomial f as a multivariate polynomial in the coefficients of f and study for which substitutions of the variables the discriminant is a square. This technical result has been given in [8,Lemma 5.2], which in fact implies an explicit result. Here, we reproduce the proof briefly.…”
Section: Preliminariesmentioning
confidence: 61%
“…, Y d ) depends on some variable Y i . The result in [8,Lemma 5.2] comes from the sum of three upper bounds…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also noted in the introduction that Odoni [11] studied the stability of additive polynomial f (x) = x p − x − 1 over F p . His method is different from the methods of the current paper and those of [1,7]. Using Capelli's lemma he showed that the Galois group of f f (x) over F p is the cyclic group of order p and hence f f (x) is not stable.…”
Section: Discussionmentioning
confidence: 74%